2006
DOI: 10.1109/tvcg.2006.15
|View full text |Cite
|
Sign up to set email alerts
|

Thin structure segmentation and visualization in three-dimensional biomedical images: a shape-based approach

Abstract: This paper presents a shape-based approach in extracting thin structures, such as lines and sheets, from three-dimensional (3D) biomedical images. Of particular interest is the capability to recover cellular structures, such as microtubule spindle fibers and plasma membranes, from laser scanning confocal microscopic (LSCM) data. Hessian-based shape methods are reviewed. A synthesized linear structure is used to evaluate the sensitivity of the multiscale filtering approach in extracting closely positioned fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The two methods are complementary, as the leaflets may not always be accurately segmented out by the dynamic contour approach, and the heart walls and valve annulus are generally not found by the thin tissue detector. The thin tissue detector models the local TEE intensity as Gaussian and then performs an analysis of the disparities of the eigenvalues associated with the intensity Hessian [25]. If one these eigenvalues is small when compared to the other two, this suggests the presence of a sheet or thin tissue structure.…”
Section: Valve Segmentationmentioning
confidence: 99%
“…The two methods are complementary, as the leaflets may not always be accurately segmented out by the dynamic contour approach, and the heart walls and valve annulus are generally not found by the thin tissue detector. The thin tissue detector models the local TEE intensity as Gaussian and then performs an analysis of the disparities of the eigenvalues associated with the intensity Hessian [25]. If one these eigenvalues is small when compared to the other two, this suggests the presence of a sheet or thin tissue structure.…”
Section: Valve Segmentationmentioning
confidence: 99%
“…Li et al [LWP * 04] proposed a fitting method using ellipsoids for implicit surfaces with a limited number of data points. Recently Huang et al [HFBC06] showed a shape-based approach for thin structure segmentation and visualization in biomedical images using an ellipsoidal Gaussian model.…”
Section: Related Workmentioning
confidence: 99%
“…Given the eigenvalues λ 3 ≤ λ 2 ≤ λ 1 of the 3 × 3 Hessian matrix for each 3D image pixel, it is possible to compute a likelihood of the pixel being part of a linear structure [23,24]. This measure, which we …”
Section: Vessel Enhancementmentioning
confidence: 99%
“…This vesselness υ has been used before to improve visualizations of linear structures [23,24], but we are using it to assist in vessel tracking. However, other similar equations have been used for vessel identification before [25].…”
Section: Vessel Enhancementmentioning
confidence: 99%